2009
DOI: 10.1083/jcb.200804154
|View full text |Cite
|
Sign up to set email alerts
|

A CD317/tetherin–RICH2 complex plays a critical role in the organization of the subapical actin cytoskeleton in polarized epithelial cells

Abstract: CD317/tetherin is a lipid raft–associated integral membrane protein with a novel topology. It has a short N-terminal cytosolic domain, a conventional transmembrane domain, and a C-terminal glycosyl-phosphatidylinositol anchor. We now show that CD317 is expressed at the apical surface of polarized epithelial cells, where it interacts indirectly with the underlying actin cytoskeleton. CD317 is linked to the apical actin network via the proteins RICH2, EBP50, and ezrin. Knocking down expression of either CD317 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 65 publications
(105 reference statements)
4
126
0
1
Order By: Relevance
“…3C) of SIVtan Env. When expressed alone in 293T cells, HA-tagged tetherin localized at the cell surface, as well as in intracellular compartments, consistent with previous observations (8,19,20). On co-expression of SIVtan Env the tetherin was now mostly intracellular with a perinuclear distribution.…”
Section: Sivtan Env Does Not Reduce Total Tetherin Levels But Depletessupporting
confidence: 89%
“…3C) of SIVtan Env. When expressed alone in 293T cells, HA-tagged tetherin localized at the cell surface, as well as in intracellular compartments, consistent with previous observations (8,19,20). On co-expression of SIVtan Env the tetherin was now mostly intracellular with a perinuclear distribution.…”
Section: Sivtan Env Does Not Reduce Total Tetherin Levels But Depletessupporting
confidence: 89%
“…has been proposed to link lipid rafts to each other and to the actin cytoskeleton (19,40), whereas HIV assembly sites are known to include both lipid rafts and TEMs (20 -22). In light of this, we wondered whether the displacement of BST2 from viral assembly sites by Vpu might disrupt the organization of membrane microdomains at assembly sites.…”
Section: Vpu Does Not Reorganize Membrane Microdomains During the Dismentioning
confidence: 99%
“…In support of this, we show using immunofluorescence microscopy that Trp-76 is required for the displacement of BST2 from viral assembly sites by Vpu. Because BST2 has been proposed to link lipid rafts to each other (4,18) and to the actin cytoskeleton (19), we considered that Vpu might distort the membrane topology of viral assembly sites through its influence on BST2. Instead, we observed that cellular markers of lipid rafts and tetraspanin-enriched membrane domains (TEMs), proteins that define the assembly sites of HIV-1 virions (20 -22), remained associated with Gag, the viral structural protein that drives viral assembly, despite the Vpu-induced redistribution of BST2.…”
mentioning
confidence: 99%
“…This places the N-terminal cytosolic domain of tetherin in a suitable position to interact with the actin cytoskeleton, which it does (indirectly) (Rollason et al, 2009). Consistent with this interaction is the fact that knocking down expression of tetherin in polarised epithelial cells leads to a complete loss of the sub-apical cortical actin network and a commensurate loss of apical microvilli (Rollason et al, 2009).…”
Section: Introductionmentioning
confidence: 99%